Networks of Revolutionary Workers: Socialist Red Women in Finland in 1918 - Lintunen Tiina; Elo Kimmo (Cambridge University Press, 2022)
Revolutions need people. How do these people connect with each other, and how can the revolutionary message pass from one person to another? This article aims to answer these questions by examining the revolutionaries who participated in the Finnish Civil War on the rebellious Red side in 1918. We have chosen Red women from a particular district in Finland in order to analyse their connections and the networks created by membership of the labour movement, place of residence, and kinship. In order to see the layers of those connections, we utilize historical social network analysis rooted in digital history. This allows us to observe the significance and impact of regional, social networks and improves our understanding of structural factors affecting the intra-group dynamics among these revolutionary women. Our results support the claim that historical network analysis is a suitable tool for exploring interaction patterns and social structures in the past, and to gain new insights into historical phenomena.